Predictive modelling of marine fish landings in Malaysia - Rusiman, Mohd Saifullah; Sufahani, Suliadi Firdaus; Mohd Robi, Nur Afifi Izzati; Abdullah, Abdul Wahab; Azmi, Nur Amira (Pushpa Publishing House, 2018)
The fisheries sector plays an important role in the economy as a major source of food, employment and income in Malaysia. In this study, the future number of marine fish landings in Malaysia will be predicted. The monthly data from January 2005 until December 2014 were taken from Department of Fisheries Malaysia, Ministry of Agriculture and Agro-Based Industry Malaysia. The aims of this study are to predict the landing of marine fish in Malaysia by using Box-Jenkins and HoltWinters and to make a comparison between two models in order to find the better model for prediction of marine fish landings in Malaysia. Data for the number of marine fish landings is a trend pattern. Box-Jenkins and Holt-Winters approach will be applied to the number of marine fish landings. In this study, the forecast accuracy of Box-Jenkins and Holt-Winters approach has been compared by using the mean square error (MSE) and mean absolute percentage error (MAPE). The better model obtained from Box-Jenkins approach was SARIMA(2, 1, 0)(0, 1, 1)12. For Holt-Winters, additive model is chosen since the MSE and MAPE values are lower. After comparing the Box-Jenkins approach and additive Holt-Winters, it is found that additive Holt-Winters is a better method with a lower value of MSE and MAPE and could be used by fisheries managers and scientists to decide on sustainable management issues.